Mapping Awareness of Halal Cosmetics Brands in the Teenagers Segment of Bandung City - Muhsin Muhsin (International Journal of Nusantara Islam, 2019)
There are many factors that can explain why the consumer market for halal products is now growing fast, among others, because the profile of the younger generation of Islam is now more religious thanks to the rapid flow of information, awareness, knowledge and concern for halal consumption. One component of brand strength is brand awareness, which is how well consumers know or know about a brand. Therefore, brand awareness is a key determinant of building brand equity. When products are in the early stages of growth, such as halal cosmetics, which are new players in the cosmetics business, brand awareness is important to encourage this growth. The first research problem departed from the central phenomenon of how teenagers actually aware of halal cosmetics in the city of Bandung, and which halal cosmetic brands are best known? Associated with the issue of brand strength, then more specifically the problem of this research is how strong are teenagers aware of some halal cosmetic brands that are circulating in the city of Bandung, high, medium or low? Then is this brand awareness related to consumer demographic factors? Then is this brand awareness related to loyalty to halal cosmetic brands? The results showed that adolescents in the city of Bandung who require to use cosmetics labeled halal because they are aware of religious values, one of which as a form of Islamic law is included in rational instrumental actions. Then interpret cosmetics labeled halal as a form of carrying out Islamic law because it is protected from material that is haram and will not affect worship. Teenagers in Bandung City who are not based on using cosmetics labeled halal because they prefer cosmetics based on their needs and price and quality are included in instrumental rational actions. Then interpret halal labeled cosmetics as cosmetics that are safe for the skin because they do not cause irritation, cosmetics that are protected from prohibited ingredients, cosmetics that have no difference with other cosmetics.